(untitled) (Research, Society and Development, 2022)
The aim of the present study was to investigate the protocols used in physical training in people with visual impairments. The referent research was a study in which an integrative literature review was carried out, using a qualitative approach, of a descriptive nature. The search and location of data was carried out in the PubMed, LILACS and SciELO databases, with the descriptors “Physical Training” AND “Visual Impaired” and “Physical Training” OR “Visually Impaired” “Physical Exercise” AND “Visually Impaired” in the Portuguese, English and Spanish languages, between the years 2017 and 2021. For data collection and analysis, the validated Ursi instrument and the PRISMA flowchart were used. A total of 522 studies were retrieved, of which 15 articles make up the final qualitative synthesis. The protocols used in training for the visually impaired include exercises that work strength, balance, flexibility, as well as a focus on social inclusion. Most studies sought to highlight the importance, difficulties and lack of studies on the practice of some sport or physical activity for people with visual impairments. However, it is clear that the modalities used through the specific protocols improved the quality of life of the visually impaired. There is a bias in publications on this topic, focused on the specifics of protocols used for a long period of training and, mainly, for people with visual impairments.